2014
DOI: 10.1007/s11270-014-2242-0
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde Removal from Airstreams Using a Biofilter with a Mixture of Compost and Woodchips Medium

Abstract: The performance of a laboratory-scale biofilter packed with a mixture of compost and woodchip on formaldehyde removal from polluted air streams was investigated. The reactor was inoculated with aerobic sludge as a source of bacteria, obtained from a municipal wastewater treatment plant. A nutrient solution was daily added to the reactor media. An airflow containing different concentrations of formaldehyde (from 20±2 to 276± 5 mg m −3 ) was introduced into the reactor. In inlet formaldehyde concentration, an av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
(53 reference statements)
2
11
0
Order By: Relevance
“…On the other hand, in high values of EBRT, a larger volume may be needed; thus the investment cost of the biofilter may be increased . Rezaei, Fazlzadehdavil and Hajizadeh found that the average removal of FA using a biofilter with a mixture of compost and woodchips medium was 91% at an EBRT of 180 s and inlet concentrations of 20–276 mg m ‐3 . In this study, the average removal of FA was 94.9% at an EBRT of 120 s and inlet concentrations of 1.2–11 mg m ‐3 .…”
Section: Resultssupporting
confidence: 79%
“…On the other hand, in high values of EBRT, a larger volume may be needed; thus the investment cost of the biofilter may be increased . Rezaei, Fazlzadehdavil and Hajizadeh found that the average removal of FA using a biofilter with a mixture of compost and woodchips medium was 91% at an EBRT of 180 s and inlet concentrations of 20–276 mg m ‐3 . In this study, the average removal of FA was 94.9% at an EBRT of 120 s and inlet concentrations of 1.2–11 mg m ‐3 .…”
Section: Resultssupporting
confidence: 79%
“…18,27 On the other hand, the enzymatic bioremediation is highly selective to FA and can convert this waste into nontoxic products under ambient conditions. In this field, compost extracts, 28 i.e., FA-degrading microorganisms like fungi 29,30 or bacteria, 31 or purified specific enzymes were employed for FA abatement. 32 However, maintaining the stability and activity of the biocatalyst is challenging under gaseous conditions, 28,32 which currently limits their use to FA waste water remediation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although promising, room-temperature degradation of FA is only possible with some expensive noble-metal catalysts and their efficiency was not proven at a low FA concentration (<ppm). , (Photo)­catalytic oxidation methods are however nonselective to FA and degrade any organic compounds with the formation of radicals able to react with other substances with the risk of formation of harmful byproducts. , On the other hand, the enzymatic bioremediation is highly selective to FA and can convert this waste into nontoxic products under ambient conditions. In this field, compost extracts, i.e., FA-degrading microorganisms like fungi , or bacteria, or purified specific enzymes were employed for FA abatement . However, maintaining the stability and activity of the biocatalyst is challenging under gaseous conditions, , which currently limits their use to FA waste water remediation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological air pollution controls, which are a suitable alternative to conventional physico-chemical technologies, can convert a variety of compounds (such as VOCs) through the microorganisms activities into harmless elements. Thanks to the high efficiency and environmental friendly features, they are widely used by industries (Hort et al 2014;Li et al 2015;Rezaei et al 2014).…”
Section: Introductionmentioning
confidence: 99%